USE OF INJECTABLE MELOXICAM (AMELOTEX®) FORMULATION IN PATIENTS WITH GONARTHROSIS - M S Eliseyev; M S Barskova; S A Vladimirov (Современная ревматология)
The paper presents the results of a study of the efficiency and safety of using the nonsteroidal anti-inflammatory drug Amelotex® (international nonproprietary name meloxicam) in patients with osteoarthrosis. A short course of therapy with the drug is demonstrated to have a good analgesic effect, to be well tolerated, and to result in better quality of life in patients with gonarthrosis.